Reducing the Impact of Low Quality and Resolution Speed Sensor on Digital Speed Servo Control System Utilizing a Speed Observer (Journal of Academic Research, 2025)
In this paper, the impact of the low resolution and quality speed sensor on the performance of a speed feedback servo control system is studied, in terms of the error between the set point and the actual output.  Therefore, a low quality speed sensor is designed based on the computation of the speed signal by the derivation of the low resolution incremental quadrature encoder-decoder position signal, the sensor is then implemented in a speed feedback servo control system and compared to a system with an ideal sensor, next, the sensor low quality speed signal is enhanced by designing and implementing a speed observer to estimate the speed signal based on speed measurement first, second, the speed observer is extended to be based on position measurement, where the second observer outperforms the first one.  Moreover, the control algorithms based on the developed second observer are also applied on a real hardware experiment successfully in real time control.